Testing Weak-Form Efficiency of The Chinese Stock Market and Hong Kong Stock Market - Lei, Zhuolin (2012)
This study examines the random walk hypothesis to determine the validity of weak-form efficiency for Shanghai, Shenzhen and Hong Kong Stock Exchanges. Daily returns from 2001-2010 for Shanghai A and B shares, Shenzhen A and B shares and Hong Kong Hang Seng Index are used in this study. The random walk hypothesis is examined by using four statistical methods, namely a serial correlation test, an Augmented Dickey-Fuller Unit Root test, a runs test and a variance ratio test.